Evaluation of Calcium Nutrition in Okra - Giffy Thomas (Department of Agronomy , College of Agriculture, 2019)
The investigation on “Evaluation of calcium nutrition in okra (Abelmoschus esculentus (L.) Moench)” was undertaken with the objectives to develop and characterize an organic calcium source for foliar spray and to identify the best source and method of calcium nutrition, thereby assessing its impact on growth, productivity, profitability and quality of okra. The study was conducted in two experiments. Experiment I was done to develop and characterize an organic calcium source for foliar spray at College of Agriculture, Padannakkad. The field experiment was intended for the evaluation of source and method of calcium application in okra at Regional Agricultural Research Station, Pilicode during 2017-2018. The first investigation was laid out in completely randomized design with three treatments replicated five times. The resultant solutions were obtained by dissolving egg shells (T1), bone pieces (T2) and powdered lime shell (T3) in coconut water vinegar used as solvent. Perusal of the results indicated that the solutions were acidic. The calcium content was highest with solutions extracted from lime shell followed by eggshell. The maggot development was observed earlier in solutions extracted from lime shells and bone pieces (2 DAF) than egg shells (15 DAF). The solution prepared from egg shells are preferred to those from bone pieces and lime shell due to its easy availability and relatively longer period of storage. Hence the solution prepared from egg shells can be used as a source of calcium for foliar spray like calcium nitrate and calcium chloride available in market as foliar fertilizers. The field experiment was carried out in randomized block design with nine treatments and three replications. The treatment combination were, KAU POP (T1), Organic POP (T2), KAU POP + lime as soil application (T3), KAU POP + dolomite as soil application (T4), KAU POP + foliar spray of one per cent calcium nitrate (T5), KAU POP + foliar spray of 0.5 per cent calcium chloride (T6), KAU POP + foliar spray of 0.5 per cent calcium acetate (T7), KAU POP + foliar spray of organic calcium extracted from egg shell (T8) and KAU POP + foliar spray of coconut water vinegar (T9). The foliar sprays were given at 30, 45, 60 and 75 DAS. Considering the yield and yield attributes, the highest fruit weight was exhibited by T6 and was statistically on par with T5 and T7. The treatment T5 recorded maximum number of fruits per plant (38.94), yield per plant (0.657 kg) and total fruit yield (24.93 t ha-1) and was statistically on par with all treatments except T2, T1 and T9. Foliar application of calcium chloride and calcium nitrate along with KAU POP increased fruit and plant dry matter production significantly over other treatments. Organic carbon, available form of nitrogen, magnesium, boron and zinc in soil did not differ with treatments. The maximum value for soil available potassium and calcium was with T3 followed by T4. The highest calcium content in the plant was observed in T5 and it was on par with T6 and T7. T9 recorded lowest calcium content in plant. The fruit calcium content was highest with T6 and it was statistically on par with T7, T8 and T5. Foliar application of calcium nitrate and calcium chloride significantly increased calcium uptake by plants over other treatments. The calcium uptake by fruits was maximum in T6. The shelf life of fruits was highest in T6 (7.33 days) and was on par with T5, T7 and T8. The larval incidence of leaf roller was lowest with T5 and was on par with T7, T8, T6 and T9. The highest net returns (Rs. 3.38 lakh ha-1) and BCR (3.29) was obtained in T6 and was on par with T5, T4, T7 and T3. Therefore it can be concluded from the study that application of calcium along with recommended dose of nutrients (110:35:70 kg NPK ha-1) either through soil or as foliar spray has a significant role in maximizing the yield of okra. However foliar application of 0.5 per cent calcium chloride or one per cent calcium nitrate is beneficial for getting higher yield per unit area and maximum economic returns. Moreover this nutrient schedule is economically viable and maintaining soil fertility.